PENGARUH LINGKUNGAN KERJA FISIK, KEPEMIMPINAN SITUASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN LPD DESA ADAT KEROBOKAN - Anak Agung Made Sintya Yustina; Ni Nyoman Suryani; I Nyoman Mustika (EMAS, 2022)
This study aims to determine the effect of the physical work environment, situational leadership and work motivation on employee performance. The research was conducted at the LPD Desa Adat Kerobokan. The population and sample in this study were 42 employees of the LPD Desa Adat Kerobokan. Data was collected by observation, study of documentation, questionnaires and interviews. Data analysis was performed using descriptive analysis and multiple linear regression to determine the effect of the physical work environment, situational leadership and work motivation on employee performance. The results of the analysis show that the physical work environment, situational leadership and work motivation have a positive and significant effect on employee performance where if the physical work environment, situational leadership and work motivation increase, employee performance will increase.